Perencanaan Tahapan Persiapan Dan Perhitungan Reklamasi Di Lahan Bekas Tambang Air Rikai PT Timah Tbk Kabupaten Bangka: Planning for Preparatory Stages and Reclamation Calculations on the Former Air Rikai Mine Land of PT Timah Tbk, Bangka Regency - Zahrah, Salsabila Oldia; Franto, Franto; Mardiah, Mardiah (MINERAL, 2024)
The research location chosen was the Air Rikai ex-mining land, which is an alluvial ex-mining land within the IUP of PT Timah Tbk. The negative impact that arises from mining is in the form of land damage. This research aims to overcome damage and also ensure that reclamation activities can be carried out well. The method used in this research is a quantitative method. The data taken is in the form of soil samples, soil pH and water pH data, topographic data (x,y,z coordinates) and bathymetric data for the depth of the pit. The results of data processing and analysis show that the condition of the land to be reclaimed has an area of 13 Ha and is divided into 2, namely voids with a total area of 1.57 Ha and land area of 11.43 Ha. Land use is carried out by stockpiling overburden with a required volume of overburden of 35,511.54 m³. Land leveling with a volume of pushed soil of 35,280 m³. Arrangement of the edge of the pit with a volume of soil moved of 230.29 m³. Construction of drainage channels with an excavation volume of 214.59 m³. Installation of concrete buis type culverts with dimensions of 50 x 50 cm and a length of 50 cm. In the revegetation, 1,517 oil palm trees were planted, then 463 sea cypress trees were planted along the underside and LCC seeds to help loosen the soil. Treating acid mine drainage with 350 water hyacinths. The costs required for reclamation are divided into 2, namely, Direct Costs and Indirect Costs. The direct costs required are IDR 679,286,160 and the indirect costs required are IDR 213,975,140. The total costs required for reclamation of land with an area of 13 Ha are IDR 893,261,300.